Student Engagement and Satisfaction with Online Learning: Comparative Eastern and Western Perspectives - Fang, Marcela; Choi, Kijung; Kim, Soojung; Chan, Bing (Journal of University Teaching and Learning Practice, 2023)
This study investigated the antecedents of student engagement in online learning and the consequent impact on higher education students’ satisfaction with online learning. More specifically, a structural model was proposed to examine students’ perceptions of adaptability, interactivity, computer/ Internet self-efficacy and psychological safety as key factors impacting their engagement with online learning tools and satisfaction with the online learning experience. A self-administered online survey was conducted with 539 undergraduate students in China, Australia, and South Korea. Structural equation modelling and multigroup analysis were used to test the study’s hypotheses. The findings indicated that the proposed four antecedents significantly impacted their engagement with online learning tools, influencing their overall satisfaction with the online learning experience. In addition, this study found significant differences between the relationships of the four antecedents of engagement with online learning tools among students in China, Australia, and South Korea, influencing their satisfaction with the online learning experience. The study concludes with theoretical and practical implications informing future institutional practices.